2022
DOI: 10.1101/2022.06.10.495620
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lineage-specific, fast-evolving GATA-like gene regulates zygotic gene activation to promote endoderm specification and pattern formation in the Theridiidae spider

Abstract: BackgroundThe process of early development varies across the species-rich phylum Arthropoda. Owing to the limited research strategies for dissecting lineage-specific processes of development in arthropods, little is known about the variations in early arthropod development at molecular resolution. The Theridiidae spider, Parasteatoda tepidariorum, has its genome sequenced and could potentially to contribute to dissecting early embryonic processes.ResultsWe present genome-wide identification of candidate genes … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 101 publications
0
1
0
Order By: Relevance
“…New marker genes identified for these clusters were consistently expressed in the endoderm and mesoderm (Supplementary Table S4, Supplementary Figure S2). The endodermal markers identified by this single-cell transcriptome analysis of late stage 5 embryos largely overlapped genes identified by comparative transcriptome analyses using stage-3 and stage-5 embryos depleted of activity of a novel gata-family gene in another study (Iwasaki-Yokozawa et al, 2022). The two separate studies revealed a consistent endodermal gene set.…”
Section: Single-cell Transcriptome and Clustering Of Cellsmentioning
confidence: 61%
“…New marker genes identified for these clusters were consistently expressed in the endoderm and mesoderm (Supplementary Table S4, Supplementary Figure S2). The endodermal markers identified by this single-cell transcriptome analysis of late stage 5 embryos largely overlapped genes identified by comparative transcriptome analyses using stage-3 and stage-5 embryos depleted of activity of a novel gata-family gene in another study (Iwasaki-Yokozawa et al, 2022). The two separate studies revealed a consistent endodermal gene set.…”
Section: Single-cell Transcriptome and Clustering Of Cellsmentioning
confidence: 61%